2017
DOI: 10.18632/oncotarget.20815
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunohistochemistry for SMAD4 and Runt-related transcription factor 3 may identify a favorable prognostic subgroup of pancreatic ductal adenocarcinomas

Abstract: PurposesSMAD4/DPC4 mutations have been associated with aggressive behavior in pancreatic ductal adenocarcinomas (PDAC), and it has recently been suggested that RUNX3 expression combined with SMAD4 status may predict the metastatic potential of PDACs. We evaluated the prognostic utility of SMAD4/RUNX3 status in human PDACs by immunohistochemistry.Materials and MethodsImmunohistochemical stains were performed for SMAD4 and RUNX3 on 210 surgically resected PDACs, and the results were correlated with the clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Su et al reported that TF 7 served as a poor prognostic marker of glioblastoma multiforme by enhancing proliferation by upregulating c-myc [9]. Lee et al suggested that combination immunohistochemistry for SMAD4 and runt-related TF 3 may determine a favorable prognostic subgroup of pancreatic ductal adenocarcinomas [10]. Fan et al reported that microRNA-301a-3p overexpression may contribute to cell invasion and proliferation by targeting runtrelated TF 3 in prostate cancer [11].…”
mentioning
confidence: 99%
“…Su et al reported that TF 7 served as a poor prognostic marker of glioblastoma multiforme by enhancing proliferation by upregulating c-myc [9]. Lee et al suggested that combination immunohistochemistry for SMAD4 and runt-related TF 3 may determine a favorable prognostic subgroup of pancreatic ductal adenocarcinomas [10]. Fan et al reported that microRNA-301a-3p overexpression may contribute to cell invasion and proliferation by targeting runtrelated TF 3 in prostate cancer [11].…”
mentioning
confidence: 99%